Register of Damages Caused by the Aggression of the Russian Federation in Ukraine: the Creation and Main Objectives of the Mechanism - Dąbrowska, Anna (PRAWO i WIĘŹ, 2025)
The paper addresses the ongoing issue of the financial responsibility of the Russian Federation for the damages caused by the armed attack on Ukraine in 2022. It examines the main assumptions of the recently established international compensation mechanism, the Registry of Damages in favour of Ukraine. The subsequent discussion will focus on the establishment of the mechanism, its purpose and the challenges it faces.